Intelligent Optimal Adaptive Control for Mechatronic Systems - Szuster, Marcin; Hendzel, Zenon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book deals with intelligent control of mobile robots, presenting the state-of-the-art in the field, and introducing new control algorithms developed and tested by the authors. It also discusses the use of artificial intelligent methods like neural networks and neuraldynamic programming, including globalised dual-heuristic dynamic programming, for controlling wheeled robots and robotic manipulators,and compares them to classical control methods.
Keywords: Computational intelligence; Control engineering; Robotics; Automation; Artificial intelligence; Mechatronics; Computational Intelligence; Control, Robotics, Automation; Artificial Intelligence; Mechatronics